2006
DOI: 10.1037/0022-3514.90.4.666
|View full text |Cite
|
Sign up to set email alerts
|

The social-cognitive model of achievement motivation and the 2 × 2 achievement goal framework.

Abstract: Two studies examined hypotheses drawn from a proposed modification of the social-cognitive model of achievement motivation that centered on the 2 x 2 achievement goal framework. Implicit theories of ability were shown to be direct predictors of performance attainment and intrinsic motivation, and the goals of the 2 x 2 framework were shown to account for these direct relations. Perceived competence was shown to be a direct predictor of achievement goals, not a moderator of relations implicit theory or achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
342
7
34

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(410 citation statements)
references
References 42 publications
(61 reference statements)
27
342
7
34
Order By: Relevance
“…Therefore, we considered important to control for perceived competence before examining the relations of autonomous functioning to study efforts and procrastination. Likewise, research has shown that although entity beliefs (or incremental beliefs) do not associate with perceived competence, they do predict subsequent grades, much like perceived competence does (Cury, Elliot, Da Fonseca, & Moller, 2006). So, taking into account perceived competence was again deemed necessary.…”
Section: This Studymentioning
confidence: 99%
“…Therefore, we considered important to control for perceived competence before examining the relations of autonomous functioning to study efforts and procrastination. Likewise, research has shown that although entity beliefs (or incremental beliefs) do not associate with perceived competence, they do predict subsequent grades, much like perceived competence does (Cury, Elliot, Da Fonseca, & Moller, 2006). So, taking into account perceived competence was again deemed necessary.…”
Section: This Studymentioning
confidence: 99%
“…They are learning oriented, and are motivated to try to learn, to seek out difficult conditions to develop learning, and to persist to get over these difficulties (Dupeyrat & Mariné, 2005, p.44) Both theories are summarized in Table 1 (Yeager, Paunesku, Walton & Dweck, 2013, p.5). According to the literature, the self-theory adopted by students affects their achievement and goal orientation (Dweck, 1986;Dweck, 2000;Dweck and Leggett, 1988;Elliot & Dweck, 1988;Dupeyrat & Marine, 2005;Stipek & Gralinksi, 1996;Roedel & Schraw, 1995;Blackwell, Trzesniewski, & Dweck, 2007;Aronson, Fried, & Good, 2002, Cury, Elliot, Da Fonseca, & Moller, 2006Siegle, Rubenstein, Pollard & Romey, 2010), their reactions to obstacles and difficulties (Dweck and Leggett, 1988), their motivations (Haimovitz, Wormington & Corpus, 2011, Cury, Elliot, Da Fonseca, & Moller, 2006, their strategies (Stipek & Gralinski, 1996;Vermetten, Lodewijks & Vermunt, 2005) and their efforts (Stipek & Gralinski, 1996;Dupeyrat & Mariné, 2005). Moreover, the teachers' perceptions of intelligence affect the students' success and their educational aims (Lynott and Wolfolk, 1994;Lee, 1996).…”
Section: Growth Intelligence (Incremental Theory)mentioning
confidence: 99%
“…Иако Двекова тврди да су имплицитне теорије интелигенције биполаран кон-структ, у истраживањима других аутора утврђено је да ове две теорије представљају два засебна фактора, при чему они међусобно остварују негативну корелацију (Abd El Fattah & Yates, 2006;Bodill & Roberts, 2013;Bråten & Strømsø, 2004;Cury et al, 2006;Delavar et al, 2011;Dinger & Dickhäuser, 2013;Dupeyrat & Marine, 2005), али постоје и налази у којима остварују позитивну везу (Abd El Fattah & Al Nabhani, 2012;Magno, 2012). Наведени корпус истраживања имплицитних теорија интелигенције постули-ра став да уколико је појединац присталица једне од ових теорија, то не значи нужно његов низак степен слагања са супротним становиштем.…”
Section: имплицитне теорије интелигенције: одређење појма и упитничкаunclassified